2017
DOI: 10.3390/jcdd4030009
|View full text |Cite
|
Sign up to set email alerts
|

A Multiparametric Approach Based on NT-proBNP, ST2, and Galectin3 for Stratifying One Year Prognosis of Chronic Heart Failure Outpatients

Abstract: Galectin-3 and ST2 are emerging biomarkers involved in myocardial fibrosis. We evaluate the relevance of a multiparametric biomarker approach based on increased serum levels of NT-proBNP, galectin-3, and ST2 in stratifying the prognosis of chronic heart failure (CHF) outpatients. In 315 CHF outpatients in stable clinical condition clinical and echocardiographic evaluations were performed. Routine chemistry and serum levels of NT-proBNP, galectin-3, and ST2 were also assessed. During a 12 month follow-up, cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
2
17
0
2
Order By: Relevance
“…Beyond assessment of natriuretic peptides, other biomarkers of mechanisms contributing to the pathophysiology of HF, such as inflammation (GDF‐15 and sST2), LV hypertrophy (FGF‐23), and myocardial necrosis (hsTnT), could add important prognostic information and identify patients at higher risk of events 44–47 . Studies have already demonstrated the superiority of different biomarkers combinations, including NT‐proBNP, sST2, and Galectin‐3 for risk stratification of chronic HF patients 48,49 . In 2015, we showed the additive value of FGF‐23, Galectin 3, and sST2 compared with NT‐proBNP for prediction of cardiovascular death in HFrEF 50 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Beyond assessment of natriuretic peptides, other biomarkers of mechanisms contributing to the pathophysiology of HF, such as inflammation (GDF‐15 and sST2), LV hypertrophy (FGF‐23), and myocardial necrosis (hsTnT), could add important prognostic information and identify patients at higher risk of events 44–47 . Studies have already demonstrated the superiority of different biomarkers combinations, including NT‐proBNP, sST2, and Galectin‐3 for risk stratification of chronic HF patients 48,49 . In 2015, we showed the additive value of FGF‐23, Galectin 3, and sST2 compared with NT‐proBNP for prediction of cardiovascular death in HFrEF 50 .…”
Section: Discussionmentioning
confidence: 79%
“…[44][45][46][47] Studies have already demonstrated the superiority of different biomarkers combinations, including NT-proBNP, sST2, and Galectin-3 for risk stratification of chronic HF patients. 48,49 In 2015, we showed the additive value of FGF-23, Galectin 3, and sST2 compared with NT-proBNP for prediction of cardiovascular death in HFrEF. 50 However, in the specific CORONA-HF population, a multimarker approach using a panel of 20 inflammatory and extracellular matrix biomarkers (including sST2 and galectin-3) was of limited clinical value for identifying the risk of adverse outcomes.…”
Section: Prognostic and Risk Stratificationmentioning
confidence: 96%
“…Other large-scale studies had analyzed the 5,10,27,33 potential of ST2 for predicting prognosis. Nowadays, ST2 is recognized as a marker to support risk stratification and prognosis of heart failure 1,34…”
Section: Resultsmentioning
confidence: 99%
“…ST2, галектин-3 и NT-proBNP представляют собой панель биомаркеров фиброза миокарда с частично перекрывающимися патофизиологическими механизмами действия. Повышение уровней NT-proBNP, galectin-3 и ST2 в сыворотке крови у амбулаторных больных с хронической сердечной недостаточностью в стабильном клиническом состоянии идентифицирует пациентов с самым высоким риском прогрессирования сердечной недостаточности [49]. Концентрации циркулирующего sST2 коррелируют с более тяжелым фенотипом заболевания, включая неблагоприятное ремоделирование и фиброз, сердечную дисфункцию, нарушение гемодинамики и более высокий риск прогрессирования ССЗ.…”
Section: биомаркеры фиброзаunclassified
“…Таким образом, ранний каротидный рестеноз (>50%) после КЭА с высокой вероятностью встречается у пациентов, гомозиготных по нормальному аллелю MBL2, и ассоциирован с выраженным повышением сывороточных уровней VEGF и/или PDGF после операции [122]. высокий риск иБС [113] NT-proBNP сердечная недостаточность с редуцированной фракцией выброса [49], [81], [111] сердечная недостаточность с сохранененной фракцией выброса…”
Section: биомаркеры рестенозаunclassified